ANALISIS KUTUB PERTUMBUHAN DAN PENGARUH DESENTRALISASI FISKAL TERHADAP PERTUMBUHAN EKONOMI DAERAH PEMEKARAN DAN NONPEMEKARAN DI PROVINSI SULAWESI TENGGARA TAHUN 2002-2011 - , La Ode Alisyah, Prof. Mudrajat Kuncoro, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The main objective of this study was to analyze the impact of fiscal decentralization to the economic growth on the expansion and non expansion areas in Southeast Sulawesi Province during the 10-year implementation period, i.e., from 2002 to 2011, in addition to know the trend of economic growth before and after expansion and to find the growth poles and underdeveloped areas in district/city of Southeast Sulawesi province. The variables used to determine the effect of fiscal decentralization to the economic growth was the degree of fiscal decentralization, the total of population, dummy and the level of agglomeration in District and City of Southeast Sulawesi Province. The method used to analyze these variables was done by applying panel least square (PLS) method with estimation technique of fixed effect model. The trend analysis was using the variables of economic growth in District and City. While, the variables used to find the growth poles and underdeveloped areas were Regional per capita income and City per capita income by using deviation standard and Gi and ô©ô¯ â statistics. The result of analysis showed that the degree variables of fiscal decentralization affected significant and negative to the economic growth especially Revenue sharing funds (DBH) and the General Allocation Fund (DAU) while the Special Allocation Fund (DAK) and Local Government Original Receipt (PAD) were not significant but positive on economic growth. The level of Agglomeration has affected significantly negative on economic growth whilst population growth was not, as for the dummy variable affected significant and negative to the economic growth in the non-expansion area whereas in nonexpansion area affected positive and significant to the economic growth. While, based on trend analysis has been increased on economic growth before and after the expansion as for the growth poles contained in Kolaka District, North Kolaka and North Konawe District while underdeveloped areas are in Buton District, Wakatobi and Bombana District.